Clinical management and knowledge of neonatal hypoglycaemia in Germany: A national survey of midwives and nurses. (8th March 2021) - Roeper, Marcia; Salimi Dafsari, Roschan; Hoermann, Henrike; Hoehn, Thomas; Kummer, Sebastian; Meissner, Thomas
Abstract : Aim: Despite being a common metabolic condition, the detection and care of neonatal hypoglycaemia in Germany largely depends on the infant's health‐care provider, rather than a national protocol. Therefore, this study aimed to evaluate midwives' and nurses' knowledge and management of neonatal hypoglycaemia and to determine the need for national guidelines. Methods: An anonymous online survey was developed and completed by 127 perinatal nurses and midwives. Descriptive statistics, Mann–Whitney‐ U, χ 2 and Fisher's exact tests were used to summarise and analyse the results. Results: In total, 82% of respondents indicated using guidelines but routine blood glucose screening for neonates at risk for hypoglycaemia was rarely reported (44%). A blood glucose concentration of 2.5 mmol/L (45 mg/dL) was considered the treatment threshold by 52% of the respondents. However, the responses to clinical scenarios showed distinct differences regarding the management of neonatal hypoglycaemia. Finally, 49% of respondents reported insufficient knowledge regarding neonatal hypoglycaemia and 77% indicated that they would advocate the implication of enhanced national guidelines. Conclusions: There is considerable variation in knowledge about the prevention, screening and management of neonatal hypoglycaemia among nurses and midwives in Germany. Enhanced guidelines and education of health‐care professionals are urgently needed to provide the best possible care to all hypoglycaemic newborns.